2016
DOI: 10.1007/s12119-016-9334-5
|View full text |Cite
|
Sign up to set email alerts
|

Family Influences on Hooking Up and Dating Among Emerging Adults

Abstract: Existing research posits that young adults navigate the developmental tasks of emerging adulthood, including sexual and romantic relationship formation, in context of geographic and social separation from families of origin. This assumption of independence reflects the ongoing focus on privileged samples to the exclusion of working class, racial/ethnic minority, and immigrant young adults, many of whom live with family through the emerging adult years. This exploratory analysis employs interview data from a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Perhaps it is not the perceived parental approval and norms or parent/guardian-child communication of sexual health/practice knowledge that matter, but the presence of parental supervision in the household. Even though their children may have grown, Allison (2016a) noted the important roles that families continue to play in shaping their young adult children’s interpersonal relationship development by conveying direct or indirect socialization messages and imposing surveillance, particularly on daughters.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Perhaps it is not the perceived parental approval and norms or parent/guardian-child communication of sexual health/practice knowledge that matter, but the presence of parental supervision in the household. Even though their children may have grown, Allison (2016a) noted the important roles that families continue to play in shaping their young adult children’s interpersonal relationship development by conveying direct or indirect socialization messages and imposing surveillance, particularly on daughters.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In‐depth qualitative interviews were also used with some regularity. For example, interviews helped to increase understanding about friends with benefits relationships (Weaver, MacKeigan, & MacDonald, ) and hookups (Allison, ) and sexual expectations and fears (Anders & Olmstead, ). In addition, studies frequently used open‐ended questions embedded within surveys (typically online surveys) to content analyze responses to identify prominent themes and subthemes.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…For commuter students, which Allison and Risman () found to be racially and socioeconomically diverse, found fewer opportunities to be involved in hookups due to work obligations, performing well in school to maintain academic responsibility, and having less time due to travel. In a later study, Allison () found in a racially and economically diverse sample of college students that family had an important influence on their opportunities to become involved in hooking up and dating. Many participants lived at home or traveled home regularly and were socialized, through family members' (i.e., parents and siblings) examples, or were more directly told to make school and career a priority over relationship formation.…”
Section: Sexual Activity In Noncommitted Relationship Contextsmentioning
confidence: 99%
“…Although some research has been done on conflicting norms about sexuality in the transition to college (Sennott & Mollborn, 2011), this research did not specifically address how past social norms and experiences may be related to how one adapts to new social norms, such as hookup cultures on college campuses. Despite the call for research on sexuality using the LCP (Carpenter, 2010), and the focus of LCP on culturally shared norms, social norms researchers typically do not look at how norms from one stage of the life course may influence behavior is later stages, nor do they explicitly consider social norms as cumulative throughout the life course (for exceptions see Allison, 2016;Lyons, Manning, Longmore and Giordano, 2015…”
Section: Research Questionsmentioning
confidence: 99%
“…These scholars argue that cultures of casual sex are mentally and physically damaging to both young men and women -but especially to young women (Stepp, 2007), although recent work has argued that casual sex can be positive for both men and women (Snapp, Ryu, and Stepp, 2015). Despite the explosion of research on hookup cultures and casual sex among college students, scholars are just beginning to examine the degree to which young adults' earlier sexual experiences and adolescent normative environments may impact their college sexual strategies and behavior (see Allison, 2016;Lyons, Manning, Longmore and Giordano, 2015).…”
mentioning
confidence: 99%